Solving Mathematics Olympiad Problems Training for Primary School Teachers in Bulukumba District: Pelatihan Penyelesaian Soal-Soal Olimpiade Matematika Tingkat Sekolah Dasar bagi Guru SD di Kabupaten Bulukumba - Assagaf, Said Fachry; Tahmir, Suradi; Dinar, Muhammad (Yayasan Ahmar Cendekia Indonesia, 2020)
This is elementary school teacher training to solve mathematics olympiad problems in Bulukumba district. The purpose of this training is to (1) provide information about mathematics olympiad in Indonesia (2) training teacher to solve mathematics olympiad problems, and (3) motivate primary teachers to conduct olympiad class in their school. The method is divided into two, namely the presentation and the independent tasks. The presentation focuses on the types of math competitions and the types of Olympic problems. Independent task aims to create and solve mathematics Olympiad problems for elementary school level. In addition, motivation was also being concerned in this training. The teachers were expected to use the problems in their mathematics class and also to identify students who potentially have ability join in mathematics competition. Abstrak Pengabdian ini berupa pelatihan olimpiade matematika tingkat Sekolah Dasar yang diperuntukkan bagi Guru Sekolah Dasar di Kabupaten Bulukumba. Tujuan pengabdian ini adalah untuk (1) memberikan pengetahuan terkait pelaksanaan olimpiade matematika di Indonesia (2) memberikan pemahaman terkait soal-soal olimpiade matematika, dan (3) memberikan motivasi kepada guru untuk melakukan pembimbingan olimpiade. Metode pelaksanaan terbagi atas dua yakni metode ceramah dan metode kerja mandiri. Metode ceramah berfokus kepada materi tentang jenis jenis kompetisi matematika dan jenis jenis soal olimpiade. Kerja mandiri bertujuan untuk membuat dan menyelesaikan soal olimpiade matematika tingkat SD. Selain itu, motivasi juga diberikan agar guru dapat mengadopsi soal tersbeut dalam kegiatan pembelajaran serta mencari bibit unggul yang dapat diikutkan untuk berkompetisi.